2021
DOI: 10.1111/raq.12563
|View full text |Cite
|
Sign up to set email alerts
|

Testicular development and spermatogenesis in fish: insights into molecular aspects and regulation of gene expression by different exogenous factors

Abstract: In fish, as in higher animals, the normal ontogenesis of the gonads is the basis for successful reproduction. Gonadal differentiation and development depend on the genetic cascade that programmes the events. Eventually, gonads become the sites for the maturation of gametes, which are originally derived from the primordial germ cells (PGCs) and form the cellular basis of reproduction. In fish hormones of the hypothalamic-pituitary-gonadal (HPG) axis regulate reproduction and fertility by promoting or inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 318 publications
0
11
0
1
Order By: Relevance
“…In the testes, these neurotransmitters can trigger a series of syntheses and secretion of sex steroids regulated by the HPG axis. Moreover, sex steroids produced by the testes feedback both positively and negatively to the brain, which in-turn finely controls gonadotropin secretion ( 74 ). In this study, several genes involved in steroidogenesis in the testes of common carp were identified, including cytochrome P450 family 11 subfamily b ( cyp11b ), hydroxysteroid 11β-dehydrogenase 2 ( hsd11b2 ), and hydroxysteroid 17-β dehydrogenase 3 ( hsd17b3 ) ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the testes, these neurotransmitters can trigger a series of syntheses and secretion of sex steroids regulated by the HPG axis. Moreover, sex steroids produced by the testes feedback both positively and negatively to the brain, which in-turn finely controls gonadotropin secretion ( 74 ). In this study, several genes involved in steroidogenesis in the testes of common carp were identified, including cytochrome P450 family 11 subfamily b ( cyp11b ), hydroxysteroid 11β-dehydrogenase 2 ( hsd11b2 ), and hydroxysteroid 17-β dehydrogenase 3 ( hsd17b3 ) ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the transcript profile of some important transcription factors required in SD and gonadal development in fish were analyzed during embryogenesis in A. salmon. The genes included gonadal somatic derived factor ( gsdf ), doublesex and mab-3 related transcription factor ( dmrt1 )), anti-Mullerian hormone ( amh ), forkhead box protein L2 ( foxl2 ) and cytochrome P450arom ( cyp19a ) [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate reproduction requires a myriad of precisely orchestrated events, including the production of oocytes in females and the production of sperm in males. Sperm are unique cells, produced through the complex process of spermatogenesis, in which there are a number of checkpoints in place to guarantee delivery of a high-quality product (Bhat et al, 2021). Gamete quality has become a focus in aquaculture and fish population studies, due to its impact on fertilization success and larval survival.…”
Section: Introductionmentioning
confidence: 99%